2015
DOI: 10.1111/maps.12492
|View full text |Cite
|
Sign up to set email alerts
|

Modal abundances of pyroxene, olivine, and mesostasis in nakhlites: Heterogeneity, variation, and implications for nakhlite emplacement

Abstract: Nakhlites, clinopyroxenite meteorites from Mars, share common crystallization and ejection ages, suggesting that they might have been ejected from the same place on Mars by the same ejection event (impact) and are different samples of the same thick volcanic flow unit or shallow sill. Mean modal abundances and abundance ranges of pyroxene, olivine, and mesostasis vary widely among different thin-sections of an individual nakhlite. Lithologic heterogeneity is the main factor contributing to the observed modalab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 44 publications
(229 reference statements)
7
66
0
Order By: Relevance
“…Perhaps, the petrographic features which distinguish this specimen from the other nakhlites (Corrigan et al. ; Tomkinson et al. ) might be consistent with a second launch site.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Perhaps, the petrographic features which distinguish this specimen from the other nakhlites (Corrigan et al. ; Tomkinson et al. ) might be consistent with a second launch site.…”
Section: Resultsmentioning
confidence: 70%
“…), this specimen differs from other nakhlites in certain petrologic features such as low modal olivine concentration, high mesostasis content, and very limited aqueous alteration (Corrigan et al. ; Tomkinson et al. ).…”
Section: Samplesmentioning
confidence: 82%
“…In this study, we determined a mesostasis abundance of 44%; other authors have reported values of 35–44% (Corrigan et al. ; Tomkinson et al. ).…”
Section: Resultsmentioning
confidence: 73%
“…() and Corrigan et al. (). Augite is found as large, sub‐mm to mm‐sized, subhedral to euhedral phenocrysts (Figs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation